Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1109/9.847103
|View full text |Cite
|
Sign up to set email alerts
|

An integrated friction model structure with improved presliding behavior for accurate friction compensation

Abstract: This paper presents a new dynamical friction model structure which allows accurate modeling both in the sliding and the presliding regimes. Transition between these two regimes is accomplished without a switching function. The model incorporates a hysteresis function with nonlocal memory and arbitrary transition curves. These last aspects prove essential for modeling presliding friction that is encountered in real physical situations. The model as a whole can also handle the Stribeck effect and stick-slip beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
271
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(291 citation statements)
references
References 20 publications
3
271
0
1
Order By: Relevance
“…However, LuGre model does not account for hysteresis behaviour. Swevers et al [72] model includes Stribeck friction in sliding, hysteretic behaviour in pre-sliding, frictional lag, varying breakaway and stick-slip behaviour, supported by experiments but does not account for material characteristics and the effect of loads on material variations. The Bliman Sorin model presented in Eq.…”
Section: Dynamic Friction Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, LuGre model does not account for hysteresis behaviour. Swevers et al [72] model includes Stribeck friction in sliding, hysteretic behaviour in pre-sliding, frictional lag, varying breakaway and stick-slip behaviour, supported by experiments but does not account for material characteristics and the effect of loads on material variations. The Bliman Sorin model presented in Eq.…”
Section: Dynamic Friction Modelsmentioning
confidence: 99%
“…Both Dahl and LuGre model are rate dependent because of which they cannot capture the reversal point memory. Swevers et al [72] uses the LuGre model which performs satisfactorily for constant sliding velocity and suggests modification to it. In LuGre model the parameter z can be interpreted as the average bristle deflection.…”
Section: Dynamic Friction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is representative for a group of models with auxiliary "internal dynamics" state variable that describes the micro-slip during the stiction phase [12]. Apart from the LuGre model, this approach is adopted, for example, in Dankowicz [8,13], Dahl [14], and Leuven [15,16] friction models. In these models, both stiction and sliding regimes are unified and governed by the same equations.…”
Section: Introductionmentioning
confidence: 99%
“…The control engineer is usually faced with a difficult tradeoff: how to balance the simplicity required to synthesize the control law while maintaining the complexity necessary for a realistic friction description. Several studies in literature can be found, ranging from the simple, static, Karnopp friction model [7], to the more complex, dynamic, Lugre model [8] and its evolutions [9].…”
Section: Introductionmentioning
confidence: 99%